W-Sn skarn deposits and related metamorphic skarns and granitoids - Kwak, T. A. P. (Teunis A. P.) (Developments in economic geology ;, 1987)
Intended as a reference for the academically-oriented geologist as well as the practising economic geologist, this book is concerned with the study of skarn deposits having anomalously high tin or tungsten contents, or both. Unlike many other books on economic geology, both economic W-Sn skarns and non-economic examples are covered, in order to enable the academically-oriented reader to grasp the full range of such deposits, and also to aid the economic geologist in distinguishing between W-Sn skarns having economic potential and those which do not. W-Sn skarns are notoriously complex,